Persuasive Strategies in Selected Brand Products’ Advertisement on Instagram: Rationalization Aspect - Fitria, Tira Nur (Journal of Pragmatics Research, 2021)
The objective of this research is to find the reason for using persuasive strategies in Selected Brand Products’ Advertisement on Instagram”.In Instagram Captions’ found in the selected brands' product, it is found the persuasive strategy used in “Mineral Water” products, “Medicine” products, “Food and Drink” products, “Household” products, and “Beauty and Skin Care” products. In “Mineral Water” products, these advertisements try to persuade consumers to focus on the quality and technology of the product used. In “Medicine” products, these advertisements try to persuade consumers to focus on the ingredients in the medicine and its uses, also tries to get consumers to focus on the causes and drugs that must be consumed. In “Food and Drink” products, these advertisements try to persuade consumers to focus on the high standards and technology to produce the product and quality of ingredients of the products that can be consumed. In “Household” products, these advertisements try to persuade consumers to focus on the ingredients in it and its benefits to be used. In “Beauty and Skin Care” products, these advertisements try to persuade consumers to focus on the ingredients in it and its benefits to be used. Those advertisements use rationalization in their persuasion strategy. Rationalization in persuasion work because the advertiser knows what the consumers’ needs and wants. There is the involvement of reasons, deep thought, making a sense and logical statements that expected can be accepted by the consumers.